What is Happiness? The Concept of Happiness in Existential Psychology and Therapy (Existential Analysis: Journal of the Society for Existential Analysis, 2007)
Happiness as experienced by ordinary people has been the object in both sociological and psychological studies. The concept of happiness used in the studies of Positive and Humanistic Psychology varies from subjective well-being, to the fulfilment of life goals. In Existential Psychology the concept of happiness has both bodily and spiritual dimensions. In this paper the concept of happiness will be analyzed and the use of it in existential psychology and therapy will be discussed. The contributions to the field of Bühler, Boss, Condrau, Heidegger and May will be examined to throw light on a vital phenomenon concerning us all.